ISSUES CONCERNING IMPORT SUBSTITUTION OF BUILDING MATERIALS IN THE CONSTRUCTION MARKET - Fatima M. Razakhanova (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Objectives The purpose of the study is to identify the specifics of the organisation of import substitution of building materials in the sectoral market and the development on this basis of programme actions that ensure the competitiveness of domestic producers in the sectoral market. Methods  During the research process, logical, statistical and comparative analysis approaches were used alongside expert evaluation. Results  It is demonstrated that the transition to import substitution is promoted by price rises of building materials due to changes in foreign currency exchange rates and the unstable situation in foreign trade relations. It is shown that, in addition to the present state of the building materials market,demand for modern technologies constitutes an additional factor determining the strategic priorities of the industry. It is proposed to create a register of innovative products in the field of building materials in the construction product market. The implementation of this programme will allow all the standardisation and technical regulation elements of the construction product market to be linked into a single system matrix.The necessity of implementing the planned policy of import substitution of construction materials in the construction product market is substantiated. Conclusion  In the context of the import substitution policy, the increase in the competitiveness of building materials provides for the expansion of the range of construction materials and an increase in the proportion of innovative goods. Adaptation of the regulatory and legal framework and norms of technical regulation for the production and use of domestic building materials and technologies will favour the promotion of innovative products in the construction product market. In view of the implementation of the strategy for the introduction of innovative technologies in the construction industry, a positive implementation of the import substitution programme in construction is expected, which will create additional jobs and lead to the emergence of new companies and enterprises under increasingly favourable conditions for domestic producers.